O PROCESSO DE TRABALHO DO SERVIÇO SOCIAL NA ASSOCIAÇÃO DE CATADORES DE MATERIAIS RECICLÁVEIS DE IJUI - ACATA - Baldissera, Luciana S.; Baldissera, Luci M.; Loeblein, Sandra R. (Salão do Conhecimento, 2013)
Resumo